Managing for Results : Civil Society Monitoring in the Dominican Republic - Carlson, Samuel; Indu, John-Abraham (World Bank, Washington, DC, 2012)
Despite being one of the fastest growing economies in Latin America and the Caribbean during the 1990s, a series of unfortunate events drove the Dominican Republic in 2003, to a rapid decline in its socioeconomic conditions. Fraud and mismanagement at the Baninter Bank, one of the country's biggest commercial banks, weakened the economy, and triggered a financial, and economic crises sector-wide in the country. These crises also coincided with the 2004 presidential elections, with intensified socio-political pressures worsening the situation. Within this background, the Bank supported a multi-sector program responsive to the social needs, particularly those related to education, health, and social assistance. The note looks at the results management in the midst of social problems, seeking to prod a responsible civil society in the country. As shown, the program and reforms were a success, responsive to the basic needs of the poor, and strengthened as well the institutional framework of social sectors.